Analysis of communication parameters for chosen LP-WAN standards = Analiza parametrów komunikacji dla wybranych energooszcz?dnych standardów o dalekim zasi?gu - Maj, Jakub; Eljasz, Dariusz; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This work presents both the theoretical description of popular LP-WAN standards and the description of tests of communication parameters of the LoRaWAN standard in relation to use of these standards in the data transmission on the Internet of Things technology. The tests in a simulation environment and were realized depending on the distance, the number of end devices and the spreading factor.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne